Surface Active Agents and Their Health-Promoting Properties: Molecules of Multifunctional Significance - Ioannis Anestopoulos; Despoina Eugenia Kiousi; Ariel Klavaris; Alex Galanis; Karina Salek; Stephen R. Euston; Aglaia Pappa; Mihalis I. Panayiotidis (MDPI AG, 2020)
Surface active agents (SAAs) are molecules with the capacity to adsorb to solid surfaces and/or fluid interfaces, a property that allows them to act as multifunctional ingredients (e.g., wetting and dispersion agents, emulsifiers, foaming and anti-foaming agents, lubricants, etc.) in a widerange of the consumer products of various industrial sectors (e.g., pharmaceuticals, cosmetics, personal care, detergents, food, etc.). Given their widespread utilization, there is a continuously growing interest to explore their role in consumer products (relevant to promoting human health) and how such information can be utilized in order to synthesize better chemical derivatives. In this review article, weaimed to provide updated information on synthetic and biological (biosurfactants) SAAs and their health-promoting properties (e.g., anti-microbial, anti-oxidant, anti-viral, anti-inflammatory, anti-cancer and anti-aging) in an attempt to better define some of the underlying mechanism(s) by which they exert such properties.